Connection of siemens PLC to labview using OPC - Mustafa, Mahfuzah (2004)
The project is to enable the Siemens PLC (Programmable Logic Control) S7-300 to comlllzlI1icate ll'ith the Lab VIETY. The cOllllllunication between S7-300 and LabT/lEW is via OPC (OLE for Process Control).Development of OPC Zlsing SI1vfATlC NET OPC Server. OPC is indusfly standard provides real plug-and-play software technology for process control and factor), alltomat ioll. OPC integrate software and hardware across spectrum of vendors easi~v. Vislla/i~ation of Festa Didactic process developed llsing LahI/l EW Festo Didactic is small .\ystem which consist actuators and sensors . The process of Festa is to make hole for three different material red plastic. black plastic and metal. PROFIBUS is a medium to tramJer datu from PLC to Lab VIEW or Lab VlEJ;V to PLC.